Residential water information management - Jacobs, H.E. (South African journal of information management, 2008)
The water fraternity is familiar with the term "water demand management" (WDM). Southern Africa is a water-stressed region, where the effective application of water is crucial in view of the government's drive to eradicate supply backlogs and improve living standards. WDM could be considered to be the illustrious progeny of the lesser 'water information management' (WIM), the latter term being uncommon in water-use circles. To decisively implement effective WDM measures, it is essential that the water service provider gains detailed knowledge of the water use on residential properties. This type of detailed focus is known as end-use modelling or micro-modelling of water use. Detail knowledge of parameters affecting urban water use and effective WIM are necessary for urban WDM programmes to be successful. Two types of data pertaining to residential water use are defined in this article, as is the term "residential water information management." The focus of this article is on the flow of information from a water user to the water manager and the use of the Internet in the process. The Internet is a convenient approach to gain end-use input parameter values. Reviews of prior end-use model development, parameter prioritization as a means to reduce the large number of input parameters, and application of the concept in a pilot project in Cape Town, South Africa, are also covered. Adapted from the source document.